EVALUASI KEPUASAN MAHASISWA TERHADAP PELAYANAN AKADEMIK FAKULTAS TARBIYAH DAN ILMU KEGURUAN IAI MUHAMMADIYAH SINJAI - Nurjannah Nurjannah (Jurnal Evaluasi Pendidikan, 2020)
This research was descriptive with a quantitative approach. Quantitative research involves measuring the level of certain characteristics. The subjects of the study were all students of the Faculty of Tarbiyah and Teacher Training, Islamic Institute of Muhammadiyah Sinjai. Data collection techniques using questionnaires and documentation. Based on the research results obtained that the evaluation of student satisfaction with academic services in the Faculty of Tarbiyah and Teacher Training based on 6 aspects of assessment namely tangibles aspects of 3.29, assurance aspects of 3.85, reliability aspects of 3.88, empathy aspects of 4.04, the responsiveness aspect is 3.81 and the information system aspect is 3.80. Based on these values, the six aspects are categorized as good. of the 6 aspects of the assessment, the highest assessment is on the assurance aspect while the aspect that needs to be improved is the tangibles aspect. Whereas the assessment of each study program the highest is Tadris Mathematics and the lowest is Arabic Education.